Development Of Curriculum Of Anatomy For BDS Students In UZ, Harare: A Survey-Based Study - Khan, Maimoona (Journal of Rawalpindi Medical College, 2023)
Objective: To evaluate and optimize the anatomy curriculum for BDS students in UZ. Study design: It is a survey-based study. Place and duration of study: A six-month study was carried out in the Anatomy Department, College of Health Sciences, University of Zimbabwe, Harare (March to August 2020). Material and Methods: A survey-based study was conducted in UZ, College of Health Sciences. To collect the data, two separate structured questionnaires were prepared. The structured questionnaires were then administered to medical faculty, BDS students of 3rd, 4th & 5th yr and practising dentists & internees, respectively. The sample size of the study was 70. Results: The data collected via the two structured questionnaires was analyzed. Analysis showed that all the stakeholders thought that the core dentistry subjects should be introduced earlier to the BDS students. Moreover, it was recommended that CBL/PBL be added to the curriculum to make the overall BDS curriculum more effective. Conclusion: The majority of the faculty members, BDS students, dentists and internees thought that the content of Anatomy for BDS students should be concise, specific and pertinent. The respondents supported the incorporation of CBL/PBL in the existing curriculum to make it more worthwhile.